Effective uses of computer-based softwares in teaching the listening skills in ESL - Normah, Yusof (2012)
The primary concern of the present study was to investigate the effective uses of computer-based software in teaching the listening skill in English as a second language (ESL) at higher education institutions. It aimed to find out if computer-based software can be used as a teacher Replacement or Supplement, either at the beginning or end of the listening lesson. In order to assess the effect of CALL-use, an Experimental Study was carried out. 80 post-SPM respondents enrolled in an Intensive English course at UniSZA (formerly known as KUSZA and UDM) were chosen for this study. Two achievement post-tests were administered for data collection. The data results were analysed using SPSS . The results of the study revealed that the way computerized material was used made a considerable effect on the achievement of the students. When it was used as a supplement at the beginning of the lesson, the students scored better results than those students received computerized treatment at the end of the lesson. When it was used as a teacher replacement, the students did not score well in the tests. The results also showed that noncomputerised treatment was effective for teaching the listening skill